2016
DOI: 10.1186/s12875-016-0545-5
|View full text |Cite
|
Sign up to set email alerts
|

The differential diagnosis of tiredness: a systematic review

Abstract: BackgroundTiredness is one of the most frequent complaints in primary care. Although often self-limiting and frequently associated with psychosocial stress, patients but also their physicians are often uncertain regarding a serious cause and appropriate diagnostic work-up. We conducted a systematic review and meta-analysis of studies reporting on differential diagnosis of fatigue in primary care.MethodsMEDLINE, EMBASE and conference abstracts were searched for primary care based studies of patients presenting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 35 publications
1
39
0
6
Order By: Relevance
“…Etiyolojisinin kabaca %70 oranında belirlenebildiği söylenebilir. Avrupa'da 6000'e yakın kişiyle yapılan bir çalışmada; nedenler olarak en ön sıralarda depresyon, viral üst solunum yolu enfeksiyonu, anemi, akut bronşit, ilaç yan etkileri ve malignitenin yer aldığı anlaşılmıştır (4…”
Section: Introductionunclassified
“…Etiyolojisinin kabaca %70 oranında belirlenebildiği söylenebilir. Avrupa'da 6000'e yakın kişiyle yapılan bir çalışmada; nedenler olarak en ön sıralarda depresyon, viral üst solunum yolu enfeksiyonu, anemi, akut bronşit, ilaç yan etkileri ve malignitenin yer aldığı anlaşılmıştır (4…”
Section: Introductionunclassified
“…This is not an unexpected finding, but the VT scale rendered a higher percentage, i.e., 21% scored 40, which is a troubling result, since tiredness is an indicator that something is not right. In a recent review of patients in primary care complaining of tiredness, it was reported that about every fifth patient had a depressive disorder [41]. Therefore, history taking, targeted at mental health and well-being, is of great importance, especially since young women with depression and stress symptoms have been reported to be at risk of using less effective contraceptive methods over time [19].…”
Section: Confounding Factorsmentioning
confidence: 99%
“…Necessary investigations include full blood count, urea, electrolyte and creatinine levels, liver and thyroid function tests, C‐reactive protein levels or erythrocyte sedimentation rate, and fasting blood glucose tests . Reassuringly, a systematic review of 26 studies examining CFS diagnosis in patients attending primary care with tiredness revealed a low prevalence of underlying medical conditions, including anaemia (2.8%), malignancy (0.6%), and other serious physical illnesses (4.3%) . Depression was diagnosed in 18.5% of patients.…”
Section: Diagnosing Cfsmentioning
confidence: 99%